Antiproliferative activities and phenolic acid content of water and ethanolic extracts of the powdered formula of Houttuynia cordata Thunb. fermented broth and Phyllanthus emblica Linn. fruit - Kumnerdkhonkaen, Piyawan (BMC Complement Altern Med, 2018)
BACKGROUND: Houttuynia cordata Thunb. and Phyllanthus emblica Linn. are native plants with medicinal and nutritive significance in Asia. The present study was aimed at evaluating antiproliferative effects on human cancer cell lines and identifying the phenolic acid composition of water and ethanolic extracts of the powdered formula of H. cordata fermented broth and P. emblica fruit. METHODS: Anticancer activity of the extracts was evaluated against HeLa, HT29, HCT116, MCF7 and Jurkat cells using an MTT assay and flow cytometric analysis of apoptosis induction and cell cycle arrest. Reverse phase HPLC was exploited for identification and quantification of some phenolic acids. RESULTS: MTT assay showed that both water and ethanolic extracts significantly decreased the viability of cancer cells in a dose- and time-dependent fashion. Based on the IC(50) values, ethanolic extract (IC(50) values = 0.12–0.65 mg/mL) was more cytotoxic than water extract (IC(50) values = 0.22–0.85 mg/mL) and Jurkat cells were the most sensitive to both extracts (IC(50) values = 0.12–0.69 mg/mL). The underlying mechanism for antiproliferative activity was apoptosis induction, especially in HT29, HCT116, MCF7 and Jurkat cells. HT29 cells were the most sensitive to extract-induced apoptosis. Ethanolic extract was more effective at inducing apoptosis than water extract. Moreover, cell cycle arrest was found to be another mechanism behind growth inhibition in Jurkat and HCT116 cells. However, these extracts were relatively less toxic to non-cancer Vero cells. HPLC analysis demonstrated that the powder mix extracts contained seven identified phenolic acids namely gallic, p-hydroxybenzoic, vanillic, syringic, p-coumaric, ferulic and sinapinic acids, where p-coumaric acid was detected in the highest concentration followed by ferulic acid. CONCLUSION: Overall, the results of this study suggest the powdered formula of H. cordata fermented broth and P. emblica fruit as an alternative medicine for cancer prevention and treatment.